1992
DOI: 10.1071/mf9921331
|View full text |Cite
|
Sign up to set email alerts
|

Recognizability of algae ingested by abalone

Abstract: Studies of the diet of abalone and other herbivorous gastropods, based on gut contents, may be biased against some species of algae, especially those that are most preferred. The blacklip abalone Haliotis rubra was fed for short periods on monospecific diets of eight algae, including red, brown and green species that span the range of preference. In addition, two preferred species were fed to abalone after one month's, one week's, or no starvation. The number of recognizable fragments of each alga per unit vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…Foale and Day (1992) observed that the rate of seaweed digestion in H. rubra did not differ significantly between animals fed daily and those starved for seven days. It can therefore be assumed, with reasonable certainty, that the three-day starvation period prior to the present trial probably did not affect the rate of digestion.…”
Section: Experimental Protocolmentioning
confidence: 72%
See 2 more Smart Citations
“…Foale and Day (1992) observed that the rate of seaweed digestion in H. rubra did not differ significantly between animals fed daily and those starved for seven days. It can therefore be assumed, with reasonable certainty, that the three-day starvation period prior to the present trial probably did not affect the rate of digestion.…”
Section: Experimental Protocolmentioning
confidence: 72%
“…However, no work has been published on the rates of digestion of formulated diets. Less digestible algal species may remain identifiable in abalone guts for more than 48 h, whereas preferred species are largely digested within 24 h (Foale andDay 1992, Day andCook 1995).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Gut contents provide information on an organism's diet in the relatively short term but can overestimate the contribution of the most recently consumed food items and those that are digested more slowly (Foale & Day 1992). Chemical tracers may provide longer-term and less biased dietary information (Iverson et al 2004), but their interpretation may be complicated if animals consume mixed diets or modify chemical signatures of their food (Peterson 1999, Kelly et al 2008.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the abundant populations of V. halioticoli and its speculated symbiotic contribution to the conversion of alginate to acetic acid in the gut of Japanese and South African abalones (Sawabe et al, 2003), V. superstes may not be able to form such associations with Australian abalones because the major food of Australian abalones is red algae (Foale & Day, 1992). Differences in feeding behaviour of host abalones may affect the microflora of the gut microbial ecosystem and select for biochemical traits of these …”
mentioning
confidence: 99%